Standards and Thresholds for Impact Assessment - Schmidt, Michael; Glasson, John.; Emmelin, Lars.; Helbron, Hendrike; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Standards and Thresholds play an important role in many stages of the Environmental Impact Assessment (EIA) process. They can be legally-binding or guidance values and are linked to environmental data. This publication provides a comprehensive collection of standards and thresholds, their derivation and application in case studies of EIA projects. The first part introduces the nature of standards and thresholds and key drivers for their determination. The book then describes, in Part II, technical standards from the perspective of EIA projects. Part III addresses the issue from the other side, environment and human health, and discusses the assessment of impacts on the sensitivity or value of environmental and health components. Part IV sets out some emerging issues for standard and threshold with reference to new sectors and with recent instruments. The book concludes in Part V with the role of monitoring, and final implementation.
Environmental Policies and Key Drivers for Setting Standards and Thresholds -- Principles and Purposes of Standards and Thresholds in the EIA Process -- Standards and Thresholds in German Environmental Law -- Standards and Thresholds for EA in Highly Polluted Areas $1 (BThe Approach of Ukraine -- Poverty and Disease Remediation in the Millennium Development Goals: Time for Kenya to Set Standards and Thresholds? -- Widening the Scope $1 (BSustainability Indicators, Legal Thresholds and Standards in Portugal -- Problems in Setting Thresholds -- Thresholds and Standards for Different Types of Projects -- Requirements on EIA Quality Management -- Environmental Impact Assessment Standards and Thresholds for Sanitary Landfills -- Standards and Thresholds for Waste Water Discharges in Mexico -- Standards for Wastewater Treatment in Brazil -- Standards for and Evaluation of Small-Scale Dam Projects in Yemen -- The Need for Developing Thresholds for the Recycling Rate of Products in Thailand -- Guidelines for SEA in Marine Spatial Planning for the German Exclusive Economic Zone (EEZ) $1 (Bwith Special Consideration of Tiering Procedure for SEA and EIA -- Standards of Implementing Renewable Energy Technologies in Cameroon -- Standards for Mining and Quarrying -- Thresholds and Standards for Different Types of Projects -- Thresholds and Standards for Tourism Environmental Impact Assessment -- Spatial Planning: Indicators to Assess the Efficiency of Land Consumption and Land-Use -- EIA Performance Standards and Thresholds for Sustainable Forest Management in Ghana -- Thresholds and Standards for Environmental Media -- Critical Loads and Levels Concept for Ecosystems -- Soil Standards and Thresholds -- Soil Background and Reference Values for PAH and PCB -- Standards and Indicators for Monitoring Impact of Disturbance on Biodiversity in a Post-Mining Area Using GIS -- Air Pollution and Climate: Standards for Particulate Matter -- Standards and Thresholds of the EU Water Framework Directive (WFD) $1 (BPhytoplankton and Lakes -- Landscape and Protected Areas $1 (BPolish Experiences -- The Use and Misuse of Noise Standards -- Assessing Environmental Impacts on Human Health $1 (BDrinking-Water as an Example -- Management of Dams in Trans-National River Basins $1 (Ba Preliminary Sustainability Impact Assessment for the Upper Elbe River Basin -- Emerging Issues -- Environmental Impact of Nano Technology on Human Health -- Ecotoxicological Risk of Human Pharmaceuticals in Brandenburg Surface Waters? -- Environmental Oxygenology and Related Thresholds and Standards -- Quantitative Threshold Values for Strategic Environmental Assessment -- Implementation -- A Method to Monitor the Implementation of Mitigation Measures in Infrastructure Projects $1 (BExemplified with a Project in the Republic of Yemen -- The Role of Environmental Management Systems in Enforcing Standards and Thresholds in the Context of EIA Follow-Up -- Consequences of EIA Prediction Uncertainty on Mitigation, Follow-Up and Post-Auditing -- Environmental Quality Standards as a Tool in Environmental Governance $1 (Bthe Case of Sweden.s
Keywords: Environment; International environmental law; Environmental law; Environmental policy; Environmental management; Environment; Environmental Law/Policy/Ecojustice.; International Environmental Law; Environmental Management; Electronic books